Mouthwash Effects on LGG-Integrated Experimental Oral Biofilms - Qingru Jiang; Veera Kainulainen; Iva Stamatova; Sok-Ja Janket; Jukka H. Meurman; Riitta Korpela (MDPI AG, 2020)
In order to investigate the effects of mouthwashes on oral biofilms with probiotics, we compared in biofilms the susceptibility to mouthwashes of probiotic Lactobacillus rhamnosus GG (LGG) and oral pathogens Streptococcus mutans, Streptococcus sanguinis, and Candida albicans. We also evaluated these pathogens' susceptibility to the mouthwashes and their recovery after mouthwash-rinsing in biofilms with/without LGG. First, 1-day-/3-day-old LGG-integrated multi-species biofilms were exposed for 1 min to mouthwashes containing chlorhexidine, essential oils, or amine fluoride/stannous fluoride. Cells were plate-counted and relative survival rates (RSRs) of LGG and pathogens calculated. Second, 1-day-/3-day-old multispecies biofilms with and without LGG were exposed for 1 min to mouthwashes; cells were plate-counted and the pathogens' RSRs were calculated. Third, 1-day-old biofilms were treated for 1 min with mouthwashes. Cells were plate-counted immediately and after 2-day cultivation. Recovery rates of pathogens were calculated and compared between biofilms with/without LGG. Live/Dead® staining served for structural analyses. Our results showed that RSRs of LGG were insignificantly smaller than those of pathogens in both 1-day and 3-day biofilms. No significant differences appeared in pathogens' RSRs and recovery rates after treatment between biofilms with/without LGG. To conclude, biofilm LGG was susceptible to the mouthwashes; but biofilm LGG altered neither the mouthwash effects on oral pathogens nor affected their recovery.